2021
DOI: 10.1016/j.conx.2021.100063
|View full text |Cite
|
Sign up to set email alerts
|

“When it comes to time of removal, nothing is straightforward”: A qualitative study of experiences with barriers to removal of long-acting reversible contraception in Western Kenya

Abstract: Objective Barriers to removal of long-acting reversible contraception (LARC) threaten reproductive self-determination, but their influence on contraceptive behaviors is not well understood. We describe perspectives of women in Western Kenya concerning LARC removal barriers. Study design We used a qualitative descriptive approach with conventional content analysis to analyze transcripts for content and themes from eight focus group discussions ( n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 24 publications
3
43
0
Order By: Relevance
“…All of these may be important explanatory factors in switch and discontinuation 44,48 . Even where contraceptive services are available and generally free, recent evidence from Kenya has shown that provider barriers to LARC removal may restrict women’s ability freely to decide to switch or stop LARC use 18 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All of these may be important explanatory factors in switch and discontinuation 44,48 . Even where contraceptive services are available and generally free, recent evidence from Kenya has shown that provider barriers to LARC removal may restrict women’s ability freely to decide to switch or stop LARC use 18 …”
Section: Discussionmentioning
confidence: 99%
“…Most contraceptive methods are readily available, with public service delivery outlets offering an average of seven different FP method types 17 ; however, nearly half of public facilities experienced a stockout of at least one method on the date of the survey 17 . Informal payments and provider bias have also been documented as barriers to women who wish to initiate, switch or discontinue contraceptive use 18–20 . Furthermore, few studies have assessed Kenyan women’s preferences for, and responses to, specific contraceptive‐induced side effects 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may begin to change as hormonal IUDs become more widely available, particularly in the public sector 15 , 16 . However, while service delivery patterns of IUD uptake have been documented in the literature, there are few studies describing women’s experiences seeking IUD removal 8 , 17 or provider experiences providing care.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical challenges are closely related to programmatic challenges associated with scaling-up the availability of both implant insertion and removal services: providing sufficient training to health care providers, including in difficult removal techniques such that providers are confident in their removal skills; ensuring that appropriate equipment and supplies are available for both routine and difficult removals; and establishing necessary referral mechanisms as needed, including for difficult removals or where providers may insert but not remove implants 5,7 . A few recent studies which document the client perspective in relation to implant removals in sub-Saharan Africa reiterate these challenges [8][9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%